2022
DOI: 10.3390/jcm11175082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bone Morphology on In Vivo Tibio-Femoral Kinematics in Healthy Knees during Gait Activities

Abstract: An improved understanding of the relationships between bone morphology and in vivo tibio-femoral kinematics potentially enhances functional outcomes in patients with knee disorders. The aim of this study was to quantify the influence of femoral and tibial bony morphology on tibio-femoral kinematics throughout complete gait cycles in healthy subjects. Twenty-six volunteers underwent clinical examination, radiographic assessment, and dynamic video-fluoroscopy during level walking, downhill walking, and stair des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Accordingly, the high-grade TPIF group included (insignificantly) more non-contact and less contact ACL injuries compared to the low-grade TPIF group. Moreover, according to the tibia morphology, some knees are probably more susceptible to pivoting than others [ 14 ]. However, it is suggestive that excessive pivoting force, while resulting in higher graded TPIF and ALC injury, should also cause increased assessable instability.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the high-grade TPIF group included (insignificantly) more non-contact and less contact ACL injuries compared to the low-grade TPIF group. Moreover, according to the tibia morphology, some knees are probably more susceptible to pivoting than others [ 14 ]. However, it is suggestive that excessive pivoting force, while resulting in higher graded TPIF and ALC injury, should also cause increased assessable instability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that LPTS is a risk factor for high‐grade pivot shift [5, 22, 32], ACL injury [6, 27], and graft failure after ACL reconstruction [8, 41]. Regarding the knee kinematics, Hodel et al [18] reported that a steeper LPTS was not related to tibial anteroposterior translation or tibial rotation during level walking in 26 healthy volunteers imaged using dynamic video‐fluoroscopy. On the other hand, Kikuchi [23] et al reported a steeper LPTS was positively correlated with the maximum tibial internal rotation during a single‐leg drop jump in patients after ACL reconstruction who were imaged using a conventional motion capture system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown increased interest in the association between bony morphology and knee kinematics [4,18,23,35]. Speciically, a steeper LPTS was associated with more tibial internal rotation during drop jumps [23,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reconstructed midsagittal plane is parallel to the cortex of lateral femoral condyle with approximately 10–15 degrees of internal rotation in the anteroposterior direction. Two circles were drawn to the bony edge and were congruent with the sphericity of the LFC [ 20 ] (Fig. 2 A).…”
Section: Methodsmentioning
confidence: 99%